2012
DOI: 10.1111/j.1600-0722.2012.954.x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium alloy surface oxide modulates the conformation of adsorbed fibronectin to enhance its binding to α5β1 integrins in osteoblasts

Abstract: Our laboratory has previously demonstrated that heat (600 °C) or radiofrequency plasma glow discharge (RFGD) pretreatment of a titanium alloy (Ti6Al4V) increases the net-negative charge of the alloy’s surface oxide and the attachment of osteoblastic cells to adsorbed fibronectin. The purpose of the current study was to investigate the biological mechanism by which these surface pretreatments enhance the capacity of fibronectin to stimulate osteoblastic cell attachment. Each pretreatment was found to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…Recently, Ti alloy has been found to provide a highly favorable surface for osteoblast adhesion and osteogenic differentiation. Rapuano et al demonstrated that Ti alloy can form a superficial oxide layer that absorbs fibronectin and promotes osteoblast attachment and osteointegration through binding of adsorbed fibronectin to surface-expressed osteoblast integrins (17). Moreover, OlivaresNavarrete et al found that culture of human osteoblast-like cells on Ti-6Al-4V can lead to enhanced osteogenic differentiation compared with PEEK (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ti alloy has been found to provide a highly favorable surface for osteoblast adhesion and osteogenic differentiation. Rapuano et al demonstrated that Ti alloy can form a superficial oxide layer that absorbs fibronectin and promotes osteoblast attachment and osteointegration through binding of adsorbed fibronectin to surface-expressed osteoblast integrins (17). Moreover, OlivaresNavarrete et al found that culture of human osteoblast-like cells on Ti-6Al-4V can lead to enhanced osteogenic differentiation compared with PEEK (15).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the titanium alloy (Titanium-6 Aluminum-4 Vanadium [Ti-6Al-4V]) can promote better osteoblast adhesion and differentiation in vitro than PEEK (15)(16)(17). Thus, Ti-6Al-4V could be a better material for cage devices, with greater potential for osteointegration.…”
mentioning
confidence: 99%
“…Titanium alloy was observed to provide a highly favorable surface for osteoblast adhesion and osteogenic differentiation. In another study, it was shown that the oxide layer adsorbed fibronectin promoted osteoblast attachment and osteointegration through binding of adsorbed fibronectin to surface-expressed osteoblast integrins [104]. Studies also reported the influence of surface nanotopography on the enhanced expression of osteogenic markers [105][106][107].…”
Section: Surface Modification Of 3d Printed Structuresmentioning
confidence: 91%
“…Ti alloy has been observed to provide a favourable surface for osteoblast adhesion and osteogenic differentiation. It can form a superficial oxide layer that promoted osteoblast attachment through binding of adsorbed fibronectin to surface-expressed integrins [22]. Another study has shown that the culture of osteoblastlike cells on Ti-6Al-4V alloy substrate could promote osteoblastic maturation by creating an osteogenic environment that contains bone morphogenetic proteins and could enhance bone formation [23].…”
Section: Metallic Materials In Orthopaedic Implantsmentioning
confidence: 99%